Early Childhood Educators’ Physical Literacy Predict Their Self-Efficacy and Perceived Competence to Promote Physical Activity - Leung, Yick Wah (Archīum Ateneo, 2023)
Research Findings Early childhood educators’ own disposition has been suggested to contribute to their ability to promote physical literacy (PL) in young children. There is currently limited evidence of educators’ own PL, and studies have not explored how PL relates to teaching knowledge and behaviors in the early childhood education (ECE) context. This current study examined the relationships of teachers’ perceived PL with their self-efficacy and perceived professional competence in relation to promoting physical activities in ECE settings. A total of 338 early childhood educators from Hong Kong responded to an online survey that consisted of the Perceived Physical Literacy Inventory (PPLI), Chinese version of the Teacher Sense of Efficacy Scale (C-TSE(R)), and Teachers’ Professional Competence (TPC) questionnaire. The findings revealed that educators’ perceived PL is moderately associated with self-efficacy and professional competence when conducting physical activities in ECE contexts. The PL attributes of self-expression and communication, and knowledge and understanding were significant predictors of educators’ self-efficacy in classroom management and teaching strategies, as well as their professional knowledge and attitudes. Practice or Policy The findings suggest that ECE teachers’ training should consider aspects of their own PL to enable their self-efficacy and perceived competence for conducting physical activities in ECE settings and thereby promote the PL of young children.